Characterization and localization of upper and lower extremity motor improvements in STN DBS for Parkinson's disease. (January 2022) - Askari, Asra; Zhu, Brandon J.; Lyu, Xiru; Chou, Kelvin L.; Patil, Parag G.
Abstract: Introduction: Subthalamic deep brain stimulation (STN DBS) may have differential effects on cardinal motor signs of Parkinson's disease (PD) in the upper and lower extremities. In addition, sites of maximally effective DBS for each sign and extremity may be distinct. Our study seeks to elucidate these structure-function relationships. Methods: We applied an ordinary least squares linear regression model to measure motor effects of STN DBS on upper (UE) and lower (LE) extremity tremor, rigidity, and bradykinesia. We then applied an atlas-independent electrical-field model to identify sites of maximally effective stimulation for each sign and each extremity. Distances between sites and statistical power to resolve differences were calculated. Results: In our study population (n = 78 patients), STN DBS improved all cardinal motor signs (β = 0.64, p < .05). Improvement magnitudes were tremor > rigidity > bradykinesia. Effects of STN DBS on UE versus LE signs were statistically equal for tremor and bradykinesia, but greater for UE rigidity than LE rigidity (β = 0.19, p < .05). UE maximal-effect loci were lateral, anterior, and dorsal to LE loci, but were not statistically resolved, despite sufficient statistical power to resolve differences of ≤0.48 mm (p < .05) between maximally effective loci of stimulation. Conclusion: STN DBS produces differential effects on UE and LE rigidity, but not for tremor or bradykinesia. This finding is not explained by distinct UE and LE loci of maximally effective stimulation. Instead, we hypothesize that downstream effects of STN DBS on motor networks and limb biomechanics are responsible for observed differences in UE and LE responses. Highlights: Subthalamic DBS improves tremor > rigidity > bradykinesia Improvement in UE rigidity > LE rigidity; tremor and bradykinesia are the same Loci for maximal effect in UE and LE cardinal signs overlap Differences in STN DBS responses are likely due to downstream network effects